Analisis pengaruh pertumbuhan ekonomi, inflasi dan suku bunga terhadap pertumbuhan UMKM di Provinsi Jambi - Dian Romadhoni; Amril Amril; Emilia Emilia (e-Journal Perdagangan Industri dan Moneter, 2020)
This study entitled the analysis of economic growth, inflation, and interest rates on the development of MSMEs in Jambi Province. To analyze Indonesia's economic growth, inflation, and interest rates on the number of MSME business units in Jambi Province in 2003 – 2018. The analytical method used in this study is a descriptive qualitative analysis and quantitative analysis. Data processing is done by using multiple linear regression. The estimation results using the statistical f test show that all variables, namely economic growth, inflation, and Indonesian interest rates, together affect the development of MSMEs in Jambi Province, with statistical t-tests showing that economic growth variables have a significant effect on MSME growth in Jambi Province, inflation has a significant impact on the growth of MSMEs in Jambi Province, and Indonesian interest rates have a substantial impact on the development of MSMEs in Jambi Province. Keywords: Economic growth, Inflation, Interest rates, MSME growth